THE INFLUENCE OF ECONOMIC FACTORS ON THE STOCK PRICE OF KIMIA FARMA COMPANIES ON THE INDONESIAN STOCK EXCHANGE - M. Subhan; Chairul Rizal; Putri Rahmayani; Hastanti Listya Ningtiyas (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This scientific work aims to analyze the effect of economic factors on the stock price of the Farma chemical company on the Indonesia Stock Exchange. This research is based on the understanding that economic factors have an important role in determining the behavior of a company's stock price.This study uses a linear regression analysis method to examine the relationship between economic factors and the stock price of the Farma chemical company. The economic factors studied included macroeconomic variables such as economic growth, inflation and interest rates, as well as microeconomic variables such as company performance and industrial factors that influenced the Farma chemical sector.The data used in this study is historical data on the stock prices of Kimia Farma companies and data related to economic factors during a certain period. Data were analyzed quantitatively using the relevant statistical software.The results of this study are expected to provide a better understanding of the influence of economic factors on the stock price of the Farma chemical company on the Indonesia Stock Exchange. These findings can be a source of information for investors, decision makers and other related parties in anticipating changes in share prices and managing investment risk in the Farma chemical sector.The conclusion of this study is expected to provide new insights about the relationship between economic factors and the stock price of the Farma chemical company. This research can also provide input for the Farma chemical company in planning a more effective and sustainable investment strategy. In addition, the results of this study can form the basis for further research in the same or related fields in the future.